Dehydrogenative Heck Annelations of Internal Alkynes - Le Bras, Jean; Muzart, Jacques (Synthesis, 2014)
This review covers the palladium-catalyzed annelations of internal alkynes through reactions leading to the loss of only two hydrogens from the substrates. They occur via (i) dual C–H bond activation, (ii) both C–H and N–H bond activation, (iii) successive amino(or oxy)palladation and C–H bond activation, or (iv) C–H bond activation followed by a Heck-type process. The proposed mechanisms are described with, in some cases, personal commentary.1 Introduction2 Synthesis of Aryl Rings2.1 Via Aryl–Alkyne Coupling2.2 Via Allylaryl–Alkyne Coupling2.3 Via Cyclopentadienyl–Alkyne Coupling2.4 Via Benzoylacetate–Alkyne Coupling 2.5 Via Indole–Alkyne Coupling2.6 Via Benzothiophene–Alkyne or Benzofuran–Alkyne Coupling3 Synthesis of Pyrrole Rings3.1 Via Imidazo[1,2-a]pyridine–Alkyne Coupling3.2 Via Aniline–Alkyne Coupling3.3 Via Enamine–Alkyne Coupling3.4 Via Enamide–Alkyne Coupling3.5 Via Indole–Alkyne Coupling and Rearrangement4 Synthesis of Pyridinone Rings4.1 Via Indole-carboxamide–Alkyne Coupling4.2 Via Arylcarboxamide–Alkyne Coupling5 Synthesis of Furan Rings6 Synthesis of Azepine Rings7 Synthesis of Spiroindenes8 Synthesis of Cyclopentadiene Rings8.1 Via Arylalkyne Self-Coupling8.2 Via Alkenylindole–Alkyne Coupling9 Conclusion
Keywords: alkynes; annulation; Heck reaction; palladium; palladacycles